Flexural behavior of reinforced masonry panels - Barros, Joaquim A. O. (2006)
A new industrialized solution for construction of reinforced brick masonry shell roofs was recently developed. Here, the influence of both the brick and reinforcement arrangements on the flexural behavior of this structural system is analyzed by carrying out four-point bending tests with reinforced masonry panels. The panel positive flexural resistance (concrete cover layer in compression) was about two times its negative flexural resistance (concrete top layer in tension). Bond between brick and concrete joints, which is the weakest link of this system, had marginal influence on the panel load bearing capacity. Shear failure was hard to obtain and seems to be of minor concern. Finally, a simple numerical model was developed to predict the deformational behavior of structures. This model reproduced, with high accuracy, the load-deflection response registered in the tested panels.